Does Education Capital and Labour Market Outcome Influence Electoral Participation and Party Affiliation Among University Students in Cameroon? (African Journal of Law and Politics, 2025)
Electoral participation is widely regarded as a key indicator of democratic legitimacy, political engagement, and constituent satisfaction. This study examines the factors that influence youth electoral apathy and the choice of political leaders within Cameroonian universities. Growing youth disengagement from voting reflects deep frustrations with governance and raises concerns about potential civil unrest. Using a stratified simple random sampling method, 825 questionnaires were administered to students from the Universities of Dschang, Yaoundé I, and Yaoundé II. Data reliability was confirmed through pre-tests, and analysis employed descriptive statistics, Spearman’s correlation, and a Probit model. Findings reveal that lower education level, belief in regime change, and party affiliation significantly increase the likelihood of abstaining from elections. Intriguingly, higher income levels were associated with a slightly increased likelihood of not voting, implying that poorer students might be more inclined to vote, possibly due to vote-buying practices. Moreover, the choice of political leader appears to be influenced by parental transmission and ethnic identity. These results have important policy implications for improving youth political inclusion in Cameroon.